Pembelajaran Bahasa dan Sastra Indonesia Berbasis Literasi Digital Ditinjau dari Kurikulum Merdeka - Dian Purnama Putri , Ragil; Febrilia, Yeyen (PGSD STKIP PGRI Pacitan, 2023)
Innovation in learning the Indonesian language and literature based on digital literacy isu urgently needed. This article aims to discover innovations in learning the Indonesian language and literature based on digital literacy for class VI elementary schools in terms of the independent curriculum. The writing method used is a literature review. The results and discussion contained in this article include. 1) making study groups; 2) watching learning videos; 3) project planning; 4) project guidance and completion; 5) settlement and exhibition; 6) report; and closing notes students gave to Mr. Soleh. In addition, digital literacy can increase students' ability to think in understanding information, increase focus, concentration, and creativity, and innovate digital literacy learning in Indonesian language learning.